2020
DOI: 10.1108/oir-05-2019-0186
|View full text |Cite
|
Sign up to set email alerts
|

Researchers' judgment criteria of high-quality answers on academic social Q&A platforms

Abstract: PurposeThrough a two-stage survey, this paper examines how researchers judge the quality of answers on ResearchGate Q&A, an academic social networking site.Design/methodology/approachIn the first-stage survey, 15 researchers from Library and Information Science (LIS) judged the quality of 157 answers to 15 questions and reported the criteria that they had used. The content of their reports was analyzed, and the results were merged with relevant criteria from the literature to form the second-stage survey q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
(73 reference statements)
0
19
0
Order By: Relevance
“…From February 1 to 14, 2020, clinical specimens including serum, nasopharyngeal and oropharyngeal swabs, urine, stool and tissues from 73 SARS-CoV-2-infected hospitalized patients were obtained in accordance with China Disease Control and Prevention (CDC) guidelines and tested for detection of SARS-CoV-2 RNA using the China CDC-standardized quantitative polymerase chain reaction assay [5]. Clinical characteristics of the 73 patients were shown in Supplementary Table 1 Gastrointestinal endoscopy was performed on a patient as described in Supplementary Case Clinical Information.…”
Section: Methodsmentioning
confidence: 99%
“…From February 1 to 14, 2020, clinical specimens including serum, nasopharyngeal and oropharyngeal swabs, urine, stool and tissues from 73 SARS-CoV-2-infected hospitalized patients were obtained in accordance with China Disease Control and Prevention (CDC) guidelines and tested for detection of SARS-CoV-2 RNA using the China CDC-standardized quantitative polymerase chain reaction assay [5]. Clinical characteristics of the 73 patients were shown in Supplementary Table 1 Gastrointestinal endoscopy was performed on a patient as described in Supplementary Case Clinical Information.…”
Section: Methodsmentioning
confidence: 99%
“…However, the measurement indicators of answer quality are different because of the situational difference of the Q&A platforms. For example, Li et al (2020) found that, on the academic Q&A platform, providing opinion, completeness and value-added are the most important measurement indicators of answer quality. Calefato et al (2015) stated that, on Stack Overflow, presentation quality, affect and reputation are important factors to predict answer quality.…”
Section: Data and Variablesmentioning
confidence: 99%
“…Another, equally widespread point of view, underlines the use of SSNS as sources of scientific knowledge [21,[40][41][42]. Researchers passively consult documents uploaded by their colleagues [19]-sometimes, unconsciously infringing the copyright [43]-or actively seek the knowledge they need through the use of features like "question and answers" [40].…”
Section: Scientific Social Networking Sites Knowledge Sharing and Knmentioning
confidence: 99%
“…SSNS are by now widespread in the academic world and have become part of the work of researchers [35]. They have been studied as means for gaining visibility and reputation [36] but also as milieus for knowledge sharing [40][41][42]88].…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation